Land use and adaptive governance under climate change: Analysis of four cases in pastoral areas of China - Zhang, Qian (Frontiers in Environmental Science, 2023)
Under the impact of climate change, pastoral areas of China have experienced increasing frequency and intensity of extreme events, which has brought more challenges to pastoralists’ livelihood. Adaptive governance refers to increasing resilience through collaborative, flexible, and learning-oriented management on different scales to form a set of political, social, economic, and administrative systems for the development, management, and allocation of resources. As such, it provides a useful framework and benchmark for enhancing adaptive capacity. However, how to implement adaptive governance in practice is still an unresolved problem. Under the current property regime, which individualized grassland use rights with wire fences built to demarcate boundaries, pastoralists of different places have tried to increase their adaptability to reduce the loss caused by disasters. Some succeeded, but some failed. Based on an analysis of four cases in pastoral areas of China, this article presents their climate change risk and changes in land use arrangements, explores the reasons for their different adaptability by comparing their coping strategies with the adaptive governance features, and finally illustrates the challenges influencing the application of adaptive governance at the local level.